Pushing the margins : women of color and intersectionality in LIS - Chou, Rose L.; Pho, Annie (Sacremento: Library Juice Press, 2018)
"Explores the experiences of women of color in library and information science (LIS), using intersectionality as a framework"--
"When I enter" : black women and disruption of the white, heteronormative narrative of librarianship / Caitlin M. J. Pollock and Shelly P. Haley -- Sisters of the stacks / Alexsandra Mitchell -- I am a Muslim, a woman, a librarian : Muslim women and public libraries / Negeen Aghassibake -- The other Asian : reflections of South Asian Americans in libraryland / Nisha Mody, Lalitha Nataraj, Gayatri Singh, and Aditi Worcester -- I am my hair, and my hair is me : #blackgirlmagic in LIS / Teresa Y. Neely -- The voice of a black woman in libraryland : a theoretical narrative / LaVerne Gray -- A woman of color's work is never done : intersectionality, emotional, and invisible labor in reference and information work / Kawanna Bright -- "Sister, you've been on my mind" : experiences of women of color in the library and information sciences profession / Alyse Minter and Genevia M. Chamblee-Smith -- Small brown faces in large white spaces / Rosalinda Hernandez Linares and Sojourna J. Cunningham -- I, too : unmasking emotional labor of women of color community college librarians / Alyssa Jocson Porter, Sharon Spence-Wilcox, and Kimberly Tate-Malone -- The burden of care : cultural taxation of women of color librarians on the tenure-track / Tarida Anantachai and Camille Chesley -- Authenticity vs. professionalism : being true to ourselves at work / Jennifer Brown and Sofia Leung -- Identity, activism, self-care, and women of color librarians / Alanna Aiko Moore and Jan E. Estrellado -- When will my reflection show? : women of color in the Kennesaw State University archives / JoyEllen Freeman -- Selection and self-identity / Robin Bradford and Stephanie Sendaula -- Reflections on the intersection of publishing and librarianship : the experiences of women of color / Charlotte Roh -- Positionality, epistemology, and new paradigms for LIS : a critical dialog with Clara M. Chu / Todd Honma and Clara M. Chu.
Includes bibliographical references and index.
Keywords: Minority women librarians -- United States; Minorities in library science -- United States; Women in library science -- United States; Intersectionality (Sociology)